Calcium Intake is Associated to Changes in the Interplay between Bone, Pancreas and Fat Tissue in the Control of Glucose Homeostasis- Experimental Study - Marotte, Clarisa (2019)
Background: Bone remodeling, insulin levels and fat mass interrelationship in glucose homeostasis control was evaluated in Weaning Normal (W) and Obese (O) rats fed High (H), Normal (N) or Low (L) Ca intakes.Methods: Glucose, Cholesterol (Chol), HDL-Chol, Triglyceride (TGL), Ca, P, insulin, Osteocalcin (OCN) and collagen C-telopeptide (CTX), body composition, BMD, BMC, body Ca and P content, perigonadal plus retroperitoneal fat (PG+RP) and liver weight were determined and HOMA-IR calculated.Results: WHCa reached the highest body fat, PG+RP and the highest CTX levels (p?0.05); WNCa had the lowest liver weight. WLCa reached the lowest body protein content (p?0.05) and the highest glucose, insulin and HOMA-IR (p?0.05). WLCa and WHCa had similar Chol levels but higher than WNCa; TGL increased and OCN decreased as dietary Ca content increased (p?0.05). OLCa presented the highest body fat, Chol and OCN levels but the lowest HDLChol levels (p?0.05); ONCa had the highest body protein percentage (p?0.05). OHCa had the lowest CTX levels (p?0.05). PG+RP, liver weight, glucose, insulin and HOMA-IR decreased as dietary Ca content increased (p?0.05). O groups reached higher adipose PG+RP fat, liver weight, glucose, insulin, Chol, TGL and HOMA-IR and lower OCN, CTX and body protein content than their matched-W groups (p?0.05).Conclusion: The relative amount of dietary Ca to P may regulate energy metabolism and bone turnover, insulin and body fat interplay in glucose homeostasis control. However, the mechanisms differ in physiological conditions or in the presence of metabolic abnormalities of energy dysregulation such as obesity and T2-diabetes.